2018
DOI: 10.1038/s41598-017-18807-8
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin gallate (EGCG) reduces the intensity of pancreatic amyloid fibrils in human islet amyloid polypeptide (hIAPP) transgenic mice

Abstract: The formation of amyloid fibrils by human islet amyloid polypeptide protein (hIAPP) has been implicated in pancreas dysfunction and diabetes. However, efficient treatment options to reduce amyloid fibrils in vivo are still lacking. Therefore, we tested the effect of epigallocatechin gallate (EGCG) on fibril formation in vitro and in vivo. To determine the binding of hIAPP and EGCG, in vitro interaction studies were performed. To inhibit amyloid plaque formation in vivo, homozygous (tg/tg), hemizygous (wt/tg), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 50 publications
0
50
0
Order By: Relevance
“…Furthermore, the T. populnea leaf contained epigallocatechin gallate and naringenin in significant amounts. These two compounds have been reported for their antioxidant, antiproliferative, and antidiabetic activities (Franko et al, ). Besides these, other pharmaceutically important polyphenols like gentisic acid, syringic acid, rutin, ellagic acid, sinapic acid, resveratrol, salicylic acid, quercetin, coumarin, cinnamic acid, and apigenin were also identified in the T. populnea leaf (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the T. populnea leaf contained epigallocatechin gallate and naringenin in significant amounts. These two compounds have been reported for their antioxidant, antiproliferative, and antidiabetic activities (Franko et al, ). Besides these, other pharmaceutically important polyphenols like gentisic acid, syringic acid, rutin, ellagic acid, sinapic acid, resveratrol, salicylic acid, quercetin, coumarin, cinnamic acid, and apigenin were also identified in the T. populnea leaf (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…NMR spectra showed line broadening of amide-proton resonances of hIAPP in the presence of EGCG (Fig.S7), which is in agreement with a recent NMR study. [12] As EGCG aggregates were detected by DLS measurements (Fig.S4) and photography (Fig.S7, right panel), binding of hIAPP (ITC analyses in Fig. 4) to EGCG aggregates was ascribed to line broadending.…”
Section: One-dimensional Proton Nmr Spectroscopy Shows Formation Of Lmentioning
confidence: 91%
“…A recent study reported morphologically distinct hIAPP aggregates in the presence of EGCG and suggested interactions between hIAPP and EGCG at the atomistic resolution. [12] Thus, to further characterize effects of Zn(II) on intermolecular interactions and phase states of EGCG as well as on hIAPP amyloid aggregation, we performed a series of one-dimensional proton NMR measurements (Fig. S7, left).…”
Section: One-dimensional Proton Nmr Spectroscopy Shows Formation Of Lmentioning
confidence: 99%
See 2 more Smart Citations